Wisata Religi Buddha Tidur di Kabupaten Mojokerto: Studi Sosio, Religi, dan Ekonomi Masyarakat - Sal Sabila Mazidatul Fiqih; Abdul Halim (Haluan Sastra Budaya, 2025)
This study examines the Sleeping Buddha religious tourism in Mojokerto Regency as a social, religious, and economic phenomenon that impacts the community. This research is motivated by the importance of religious tourism as a space for interfaith interaction and as a driver of community-based economic growth. The research method used is a qualitative ethnographic approach through in-depth interviews with several informants from each element around the toutrist area. This study applies Talcott Parsons' structural functionalism theory in combination with John Hick's theory of religious pluralism, Koentjaraningrat’s theory of cultural anthropology and the Tourism Multiplier Effect theory. The results show that the Sleeping Buddha religious tourism serves as a medium for harmonious social interaction between Buddhists and Muslims, characterized by practices of tolerance and cooperation in managing the area. From an economic aspect, 49 business units were recorded, including culinary, souvenirs, parking services, and homestays, all managed under the Tourism Village Institution (Ladewi) under the auspices of the Village-Owned Enterprise (BUMDes). This institutional mechanism allows for the distribution of economic benefits not only individually but also collectively for village development. These findings confirm that religious tourism serves a dual function: strengthening social cohesion and providing multi-layered economic impacts for the community. This research is motivated by the importance of religious tourism as a space for interfaith interaction and as a driver of community-based economic growth.